Lagos: Ownership and Identities Concept Note - Lawanson, Taibat; Eleshin, Abisoye (Lagos Ownership and Identities (Intellectual Debates and One Month Photography Exhibition), 2021)
Concept note of the project
Keywords: History; Migration; African Studies; Lagos; Knowledge